(untitled) (Journal of Human Sciences, 2025)
Mauritania possesses rich and diverse heritage assets that have, in general, contributed to improving sustainable development indicators, despite the classical approach adopted by the state in heritage management. This situation necessitates addressing heritage with a participatory vision in order to establish a rigorous strategy targeting processes of preservatin, maintenance, rehabilitation, restoration, valorization, and explorin ways to utilize heritage not only for the development of the tourism sector but also for enhancing the nationnal economic system as a whole. This article seeks to diagnose the current state of natural and cultural heritage in Mauritania and to demonstrate its contribution to achieving sustainable development. Methodologically, the study is based on fieldwork results, using diverse methodological tools. It follows scientific and practical stages, including bibliographic study, statistical research, and fieldwork, in addition to employing various cartographic and statistical techniques.